P534 Effectiveness and safety of Adalimumab switch from originator to biosimilar in patients with inflammatory bowel disease in clinical remission. (21st January 2022) - Gros, B; Soto Escribano, P; Marín Pedrosa, S; Medina Medina, R; Benítez, J M; Iglesias-Flores, E
Abstract: Background: Multiple adalimumab (ADA) biosimilars are now available since they were first commercialized in 2019 after having proved their safety and effectiveness in rheumatoid diseases. However, real data in inflammatory bowel disease (IBD) remain scarce. The main aim was to evaluate the remission rates after switching from ADA originator (Humira) to biosimilar (Hyrimoz) in a cohort of patients in remission at time of inclusion as well as to describe any safety issues. Methods: We performed a prospective, observational cohort in a tertiary IBD referral centre. All patients on Humira who were in clinical remission (defined as Harvey-Bradshaw score ≤4 or partial Mayo score ≤2) +/- biological remission (faecal calprotectin <250 μg/gr and C-reactive protein [CRP] <5gr/L) +/- endoscopic/radiologic remission at time of switch were included and followed-up for at least 9 months. Data on IBD phenotype, CRP, ADA drug and antibody levels and faecal calprotectin were collected. Results: A total of 40 patients were included, 53.7% (22) men. Median follow-up 10.6 months (IQR 10–11.1). Regarding IBD type, 85.4% (35) suffered from Crohn′s disease (CD) and 14.6% (6) from ulcerative colitis (UC). Table 1 shows the baseline characteristics of patients. Prior to switch, adalimumab levels were 7.7 mg/mL (5.9–11.2), CRP 0.4 (0–1.7) gr/L and faecal calprotectin 140 μg/gr (69–180). One patient stopped the drug (2.5%) as per personal reasons and 5% (2) flared during the follow-up but no drug cessation was needed. At the end of follow-up 94.9% (37) patients remained in clinical remission. No severe adverse events were reported. Statistical differences were found in ADA levels prior and after switching (7.7 vs 5.9 mg/mL, p=0.001), CRP levels (0.4 vs 0.7 g/L; p=0.016) and albumin levels (4.4 vs 4.6 g/L, p=0.015). Conclusion: Switching from Humira to Adalimumab biosimilar appeared to be effective and safe with most patients being in clinical remission at the end of follow-up. Statistical differences were found in adalimumab levels, CRP after switching and albumin, however, the impact of these differences was not noticeable.